Population structure, recruitment, and mortality of the freshwater crab Dilocarcinus pagei stimpson, 1861 (Brachyura, trichodactylidae) in Southeastern Brazil - Taddei, Fabiano Gazzi; Davanso, Thiago Maia [UNESP]; Castiglioni, Lilian; Herrera, Daphine Ramiro [UNESP]; Fransozo, Adilson [UNESP]; Da Costa, Rogério Caetano [UNESP] (Taylor & Francis, 2015)
Freshwater crabs of the family Trichodactylidae are widely distributed in major river basins of the South American continent. The population structure of one species, Dilocarcinus pagei, was analyzed in an artificial reservoir in Southeastern Brazil, recording data on the sex ratio, recruitment, and mortality. A total of 1339 crabs were collected and included 804 males and 535 females (3 ovigerous and 4 with hatchlings); the sex ratio was 1:0.61 (males: females). Two modes of male and female carapace width (CW) were recorded, with means of 14.4 mm (n = 407) and 38.9 mm (n = 394) for males and 17.9 mm CW (n = 269) and 39.2 mm (n = 267) for females. The mean size of males (CW = 26.6 ± 13.8 mm) was significantly larger than that of females (CW = 28.5 ± 12.8 mm). The data indicated that recruitment occurs in summer (January-March), with the reproductive period in spring (October-December), periods with the highest rainfall and temperature values in the region. Reproduction leads to the death of the parents, influencing the sex ratio, which oscillates mainly during the reproductive period.
Keywords: Crustacea; Ecology; Juvenile recruitment; Reproduction